Kajian Kitab Riyadhul Shalihin Dusun Guwah Desa Rongduringin - Takwallo (Jurnal Insan Pengabdian Indonesia, 2023)
Study of the book Riya>d} al-S{a>lih}i>n in Guwah hamlet, Rongdurin village, Tanah Merah, Bangkalan. The formulation of the problem raised in this community service activity is regarding the lack of knowledge of the people in Guwah hamlet, Rongdurin Tanah Merah Bangkalan village, about religion so that they do not know where the main sources of Islamic religious teachings themselves come from. To find alternative solutions to the above, a study of the hadith book Riya>d} al-S{a>lih}i>n was carried out in an effort to improve the quality of religious knowledge of the people of Guwah Hamlet, Rongdurin Village, Tanah Merah Bangkalan. The objectives of this PKM activity are: 1. To equip the community with knowledge directly from original sources. 2. Equipping the community with direct Islamic knowledge through history. 3. Increase the knowledge and morals of society with the substance of the book under study. The problem solving framework designed in PKM activities in the form of implementing this training activity is: 1. Periodic explanation of materials. 2. Designing a weekly study of the book Riya>d} al-S{a>lih}i>n every Sunday night. 3. Evaluation of training results. Based on interviews, questions and answers and direct observations during the activity, this community service activity yielded the following results: first, increasing community knowledge and understanding, second is equipping people with religious knowledge, third is increasing community knowledge and morals.